The use of Visual Implant Fluorescent Elastomer (VIE) for marking Phyllopezus pollicaris lizards (Squamata: Phyllodactylidae) - Paulo Ragner Silva de Freitas; Daniel Oliveira Mesquita; Frederico Gustavo Rodrigues França (Biotemas, 2013)
This study reports the use of Visible Implant Fluorescent Elastomer (VIE) and its efficiency in marking Phyllopezus pollicaris lizards from an area of caatinga in northeastern Brazil. The marking procedure of individuals was conducted from April to September 2012. Forty individuals were marked in the dorsal region with fluorescent colors (red, yellow, green and orange). Twenty lizards were recaptured and showed good retention of the elastomer. Only two specimens presented fragmented marks. The results showed that the use of VIE for tagging and recapture was efficient because of the high retention rate in the individuals recaptured and low fragmentation rate of the marks.